Triaging informative cis-regulatory elements for the combinatorial control of temporal gene expression during Plasmodium falciparum intraerythrocytic development - Russell, Karen; Emes, Richard D.; Horrocks, Paul (BioMed Central, 2015)
Background: Over 2700 genes are subject to stage-specific regulation during the intraerythrocytic development of the human malaria parasite Plasmodium falciparum. Bioinformatic analyses have identified a large number of over-represented motifs in the 5′ flanking regions of these genes that may act as cis-acting factors in the promoter-based control of temporal expression. Triaging these lists to provide candidates most likely to play a role in regulating temporal expression is challenging, but important if we are to effectively design in vitro studies to validate this role. Methods: We report here the application of a repeated search of variations of 5′ flanking sequences from P. falciparum using the Finding Informative Regulatory Elements (FIRE) algorithm. Results: Our approach repeatedly found a short-list of high scoring DNA motifs, for which cognate specific transcription factors were available, that appear to be typically associated with upregulation of mRNA accumulation during the first half of intraerythrocytic development. Conclusions: We propose these cis-trans interactions may provide a combinatorial promoter-based control of gene expression to complement more global mechanisms of gene regulation that can account for temporal control during the second half of intraerythrocytic development.